Perbandingan Produksi dan Keuntungan Petani Padi Organik dan Padi Anorganik (Studi Kasus Subak Wongaya Betan, Desa Mangesta, Kabupaten Tabanan) - NI PUTU SASRI WIRANTI; I KETUT SUAMBA; A.A.A.WULANDIRA SAWITRI DJELANTIK (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2022)
Comparison of Production and Profits of Organic and Inorganic Rice Farmers (Case Study of Subak Wongaya Betan, Mangesta Village, Tabanan Regency). The sustainability of agricultural production depends on intensive and sustainable fertilization. Currently, Indonesian families have begun to realize the importance of health and switch to healthier foods. One of the changes in rice farming is the use of organic fertilizers instead of inorganic fertilizers. The transformation of agriculture into organic farming has the potential to increase production and profits for farmers. This study aims to analyze the comparison of production and profit of organic rice farming and inorganic rice farming. Primary data was obtained by distributing questionnaires to 43 farmers applying organic fertilizers and 23 farmers applying inorganic fertilizers. Secondary data were obtained from various literatures. The results show that the average organic rice production is 6.82 tons/ha and the average profit earned is Rp. 14,169,203 per hectare in one growing season. The average inorganic rice production is 6.20 tons/ha with an average profit of Rp 7,148,203 per hectare in one growing season. The results of the t-test of production and profit, show a statistically significant difference between organic rice and inorganic rice. Farmers should consider using organic fertilizer to increase production and income which is also more environmentally friendly.